2010
DOI: 10.1007/s10562-009-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

NO Catalytic Oxidation Behaviors over CoOx/TiO2 Catalysts Synthesized by Sol–Gel Method

Abstract: CoOx/TiO 2 catalysts synthesized by sol-gel method were investigated for the oxidation of NO to NO 2 in excess oxygen. NO oxidation efficiency increased sharply as oxygen concentration increased, while NO concentration showed a negative effect. Under the conditions of 30,000 h -1 GHSV, 600 ppm NO, 4% O 2 , 9% CoOx/TiO 2 (450) had the highest NO oxidation efficiency and reached the equilibrium at 300°C with a conversion of 79.8%. The XPS results determined that Co 3 O 4 was the main active phase in 9% CoOx/TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Among these catalysts, there has been some attention focused on cobalt oxides [10] and manganese oxides [11]. It was reported that cobalt oxides possess better oxidation ability [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these catalysts, there has been some attention focused on cobalt oxides [10] and manganese oxides [11]. It was reported that cobalt oxides possess better oxidation ability [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Co 2+ /Co 3+ oxidation states were found to interconvert readily in oxidizing and reducing conditions [15]. The presence of Co 3 O 4 means high activity for oxidation reactions [10,16]. In addition, Mn-based catalysts have been proven to be highly active for the low-temperature SCR reaction, which would avoid the disadvantages associated with the commercial high-temperature catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…NO 2 is always favored over NO for NO X removal with NH 3 under oxidizing conditions [2,9]. The SCR rate can be substantially increased when a fraction of NO in the exhaust is converted to NO 2 [28].…”
Section: The Effect Of Cnts On No Oxidation Activitymentioning
confidence: 99%
“…Due to the increasing threat of NO X to the environment, many approaches have been investigated to control NO X emission. Selective catalytic reduction (SCR) technique has been proven to be one of the most effective methods for reducing NO X emissions [1,2], although selective non-catalytic reduction (SNCR) has been well applied [3]. A large number of SCR catalysts have been explored, including noble metals [4,5], transition metal oxides [2,6,7], and zeolites [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing threat of NO X to the environment, a series of methods have been developed to control NO X emission; and selective catalytic reduction (SCR) has been proven to be an effective method [1,2]. A large number of SCR catalysts including noble metals [3,4], transition metal oxides [2,5,6], and zeolite [7,8] have been optimized in literature. V 2 O 5 -TiO 2 catalysts, usually upgraded to V 2 O 5 -WO 3 /TiO 2 , have been applied extensively in the industry.…”
Section: Introductionmentioning
confidence: 99%